Kesepian Ditinjau dari Kualitas Komunikasi pada Remaja dengan Orangtua Tunggal - Rizqa Ayu Savitri; Ratna Syifa'a Rahmahana (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2009)
The purpose of this research was to examine the relations between parent's communication quality and level of loneliness in their adolescence's children. The hypothesis was the higher the quality of parent's communication with their teen children, the less lonely they would be. The respondents were high School students with 14-20 years of age from single parents' family. Data collections were using Loneliness Scales (Weiss1994; Mustikasari, 2002) and Communication Quality Scale (Laswell & Laswell, 1987; Suwantoro, 1997). Data analyzes using statistical method with Product Moment Technique from Pearson. The parent's communication quality was found to be negatively correlated to teen's level of loneliness. The higher the quality of communication between parents with their teens children, the less lonely they would become (r =-0,712; p = 0,000). The quality of communication itself contributed 50,7% to the respondents' level of loneliness while 49,3% of other factors still unidentified and need further investigation.Keywords: quality of communication, loneliness, single parent.